Influence of accommodation and refractive status on the peripheral refractive profile. Issue 9 (11th June 2009) - Davies, L N; Mallen, E A H
Abstract : Aim: The aim of the study was to determine, objectively and non-invasively, whether changes in accommodative demand modify differentially the peripheral refraction in emmetropic and myopic human eyes. Methods: Forty subjects (19 male, 21 female) aged 20–30 years (mean 22.7 (SD 2.8) years), 21 emmetropes (mean spherical equivalent refractive error (MSE) −0.13 (SD 0.29) D) and 19 myopes (MSE −2.95 (SD 1.76) D) participated in the study. Ametropia was corrected with soft contact lenses (etafilcon A, 58% water content). Subjects viewed monocularly a stationary, high contrast (85%) Maltese cross at 0.0, 1.0, 2.0 and 3.0 D of accommodative demand and at 0, 10, 20 and 30° field angle (nasal and temporal) through a +3.0 D Badal optical system. Static recordings of the accommodation response were obtained for each accommodative level, at each field angle, with an objective, open-view, infrared optometer. Results: Peripheral mean spherical equivalent ( M ) data showed that the emmetropic cohort exhibited relative myopic shifts into the periphery, while the myopic group showed hypermetropic shifts. Increasing accommodative demand did not alter the peripheral refractive profile in either the temporal (p = 0.25) or nasal (p = 0.07) periphery with no differential accommodative effect between refractive groups in either the temporal (p = 0.77) or nasal (p = 0.73) field. Significant shifts in the J 0 astigmatic component were seen in the temporal (p<0.0005) and nasal (p<0.0005) fields with increasing eccentricity. Interaction effects between eccentricity and accommodative demand illustrated that increasing accommodative demand significantly altered the peripheral refractive profile in the temporal J 0 astigmatic component (p<0.0005). The nasal periphery, however, failed to show such an effect (p = 0.65). Conclusions: Alterations in peripheral refraction augmented by changes in ocular accommodation are relatively unaffected by refractive error for young, healthy human eyes.